Вплив чехословацьких подій 1968 року на суспільні настрої країн Центральної та Південно-Східної Європи - Віруцька, С. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
У статті аналізуються реформаторські процеси 1968 року в Чехословаччині. Увагу зосереджено на впливі ідей «Празької весни» на суспільні настрої громадськості Німецької Демократичної Республіки, Болгарії, Польщі, Угорщини, Румунії і Югославії. Показано, що керівництво
країн соціалістичної співдружності в основному не поділяло прагнень
чехословацького народу до демократичних змін, надання «соціалізмові
людського обличчя», тим самим намагаючись запобігти їхньому поширенню у своїх країнах.
Зазначається, що спроби демократизації у Чехословаччині здійснювали подвійний вплив на сусідні країни, показуючи відмінність позиції
суспільства від офіційної доктрини державних структур. Міжнародна
громадськість, розуміючи взаємозв’язок подій у країнах «східного блоку»,
покладала надії, що успіх чехословацьких реформ змусить змінити існуючу обмежувальну політику і приведе до демократичних змін і у їхніх
країнах. З уведенням військ соціалістичної співдружності до Чехословаччини
1968 року, силовою акцією демократичний експеримент було припинено.
Міжнародна громадськість засудила вторгнення. Хоча «Празька весна»
й була придушена військами СРСР, НДР, Болгарії, Угорщини, Польщі,
вона стала символом спроби демократичних змін. Ідеали «Празької
весни», а саме можливості об’єднання соціалізму з демократією і громадянськими правами, глибоко укорінилися у свідомості активних кіл
громадськості держав Центральної та Південно-Східної Європи. The article analyzes reform processes of 1968 in Czechoslovakia, which
became known as the Prague Spring. Attention is focused on the influence of
the ideals and ideas of the Prague Spring on the public opinion in the German
Democratic Republic, Bulgaria, Poland, Hungary, Romania and Yugoslavia.
The author is not absorbed in the complexity of the development of the
internal political situation and the peripetia of the dialogue between the
Communist Party of Czechoslovakia and other “fraternal” parties under the
Warsaw Pact, stopping only on a general overview of the social reaction of
Central and South-Eastern Europe.
It was shown that the leadership of the countries of a socialist commonwealth
did not basically share the aspirations of the Czechoslovak people
for democratic change, “making socialism a human face”, there by trying to
prevent them from spreading in their countries.
The conclusions state that attempts to democratize in Czechoslovakia often
had a double effect on neighboring countries, showing the difference in the
position of society from the official doctrine of state structures. Recognizing the
interconnection of events in the countries of the Eastern bloc, the international
community hoped that the success of the Czechoslovak reforms would change
the existing restrictive policies and lead to positive democratic changes in their
countries.
With the introduction of the troops of the socialist community in Czechoslovakia
on August 21, 1968, a democratic demonstration was stopped by
force. The international community condemned the invasion. Although the
Prague Spring was suppressed by the troops of the USSR, the GDR, Bulgaria,
Hungary, Poland, it became a symbol of attempts at democratic change. The
ideals of the Prague Spring, namely the possibility of uniting socialism with
democracy and civil rights, deeply rooted in the consciousness of the active
public in Central and South-Eastern Europe states.